Effect of Nigella sativa oil on postoperative peritoneal adhesion formation. Issue 2 (7th October 2013) - Sahbaz, Ahmet; Ersan, Firat; Aydin, Serdar
Abstract Aim We aim to evaluate the effect of Nigella sativa oil (NSO) on postoperative peritoneal adhesion formation in female rats. This experimental study is the first on the prevention of postoperative adhesion formation by NSO. Methods Twenty‐four Wistar albino female rats were randomly assigned to three groups of eight rats each. Rats in group 1 were each injected i.p. with 1 mL of NSO. In group 2, an adhesion model was created with no injection of NSO. In group 3, an adhesion model was created and the area was covered with 1 mL of NSO. The rats were killed on postoperative day 8, and the severity of adhesions was evaluated macroscopically and histopathologically. Results There was a statistically significant difference in adhesion scores between group 2 (control) and group 3 (NSO‐treated) (P = 0.003). Statistically significant differences in angiogenesis, fibrosis and inflammation were observed between the control and Nigella sativa groups (P = 0.002, P = 0.001 and P = 0.004, respectively). Conclusion Covering peritoneal surfaces with NSO after peritoneal trauma is effective in decreasing peritoneal adhesion formation.